Reproductive decision-making following the diagnosis of an inherited metabolic disorder via newborn screening in Japan: a qualitative study - Hiromoto, Kana; Nishigaki, Masakazu; Kosugi, Shinji; Yamada, Takahiro (Frontiers in Reproductive Health, 2023)
Introduction The aim of the study was to describe the factors influencing the reproductive decision-making of carrier parents after the diagnosis of an inherited metabolic disorder in newborn screening in Japan. Methods We conducted a semi-structured interview with 12 parents and analyzed data based on content analysis methodology. Results We identified 11 factors, including personal evaluation of recurrence risk, understanding of hereditary phenomena, concerns and desires for future planned children, concerns for older siblings, perceptions of diseases, degree of acceptance and denial of diseases, the opinions of others on having another child, optimism/faith in positive outcomes, self-evaluation of parental capability, factors unrelated to the disease, and the “right” time to expand the family. Discussion Perceptions and acceptance of disease are both important factors in reproductive decision-making, though these factors fluctuate continuously during the childbearing period. Therefore, effective reproductive genetic counseling will be considerate of the parents' fluctuating perceptions on reproduction. To ensure that the decision-making process is for the benefit of the parents and future children, long-term involvement of health care professionals is needed to assess the client's acceptance of the disease and their understanding of genetic phenomena and recurrence rates.